Implementation of the Hazard Analysis Critical Control Point (HACCP) system in the green chili sauce making process at the Padang Dua Sepakat Restaurant - Putri, Indah Melati; Putri, Nabila Adinda Adriansyah (Proceeding International Pelita Bangsa, 2023)
This study investigates the implementation of Hazard Analysis and Critical Control Point (HACCP) in the production of green chili sambal, focusing on biological, chemical, and physical hazards throughout raw materials, production processes, and final products. Data were collected through observation, hazard identification, determination of Critical Control Points (CCP), monitoring cooking temperature, and sanitation records. Results indicate that cooking is the only CCP, with a critical limit of ≥100°C for at least 10 minutes. Monitoring data revealed that some batches failed to meet this limit, requiring corrective action. Sanitation records highlight the importance of equipment cleaning to prevent cross-contamination. HACCP implementation effectively ensures food safety in small-scale sambal production and provides a model for similar small food enterprises.